Pengaruh Kecepatan Pelayanan Dan Bantuan Yang Diberikan Perusahaan Terhadap Kepuasan Pemasok dan PerannyaTerhadap Loyalitas Pemasok - Adhi Wibowo (Media Aplikom, 2015)
The purpose of this study is to examine the influence of speed of service, information assistance, capital aid, and transportation assistance on rice suppliers’ satisfaction and their roles on loyalty. It uses the primary data obtained through questionnaires. The population consists of 50 suppliers; 45 of which were selected randomly as respondents. The analytical tool that used in this study is multiple regressions. The results show that the independent variables have a positive, significant effect on suppliers’ satisfaction and the suppliers’ satisfaction has a positive, significant effect on their loyalty. The coefficient of determination (R²) in the regression of speed of service, information assistance, capital assistance, and transportation assistance on the satisfaction of suppliers is 0.7017, while that of the regression of suppliers’ satisfaction on suppliers’ loyalty is 0.4516. The results imply that suppliers’ satisfaction can be increased if the company is able to improve timely service, continues to provide accurate information, provides capital assistance as needed, and provides transportation assistance; all of which should be done simultaneously. In order to maintain the suppliers’ loyalty, the management should sustain the level of suppliers’ satisfaction from various aspects.